TRANSFORMATIONAL LEADERSHIP AS A PREDICTOR TOWARDS JOB SATISFACTION AMONG FORM SIX TEACHERS IN SARAWAK - Loo, Siaw-Choon; Leh, Ling Ying (UPI Press, 2018)
This quantitative study was conducted to identify the influence of transformational leadership as a predictor of job satisfaction among Form Six teachers. A total of 148 Form Six teachers from Kuching, Sarawak through a random sampling technique were identified as respondents of the study. Data was collected by distributing questionnaires to the respondents. The questionnaire used was adapted from the previous researchers’ questionnaires. The findings show that the dimensions of individual consideration, charisma, and motivation in transformational leadership have a significant effect on job satisfaction among the teachers. Based on the findings obtained, the two-ways relations between the middle leaders and teachers need to be improved by adopting an open approach and working to understand the work-related problems.